Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's solve each part one by one to check whether the given values are solutions to the respective equations.
### Part (i)
Equation: \( x + 5 = 3 \)
Given \( x = 2 \).
Substitute \( x = 2 \) into the equation:
[tex]\[ 2 + 5 = 7 \][/tex]
The right-hand side of the equation is 3, but the left-hand side, after substitution, gives 7.
Since \( 7 \neq 3 \), \( x = 2 \) is not a solution to \( x + 5 = 3 \).
### Part (ii)
Equation: \( 8n + 5 = 21 \)
Given \( n = 2 \).
Substitute \( n = 2 \) into the equation:
[tex]\[ 8(2) + 5 = 16 + 5 = 21 \][/tex]
Both sides of the equation are equal to 21.
Since \( 21 = 21 \), \( n = 2 \) is a solution to \( 8n + 5 = 21 \).
### Part (iii)
Equation: \( 4x + 3 = 5 \)
Given \( x = -2 \).
Substitute \( x = -2 \) into the equation:
[tex]\[ 4(-2) + 3 = -8 + 3 = -5 \][/tex]
The right-hand side of the equation is 5, but the left-hand side, after substitution, gives -5.
Since \( -5 \neq 5 \), \( x = -2 \) is not a solution to \( 4x + 3 = 5 \).
### Part (iv)
Equation: \( 5p + 3 = 7 \)
Given \( p = -3 \).
Substitute \( p = -3 \) into the equation:
[tex]\[ 5(-3) + 3 = -15 + 3 = -12 \][/tex]
The right-hand side of the equation is 7, but the left-hand side, after substitution, gives -12.
Since \( -12 \neq 7 \), \( p = -3 \) is not a solution to \( 5p + 3 = 7 \).
### Part (v)
Equation: \( 4p - 3 = 13 \)
Given \( p = 1 \).
Substitute \( p = 1 \) into the equation:
[tex]\[ 4(1) - 3 = 4 - 3 = 1 \][/tex]
The right-hand side of the equation is 13, but the left-hand side, after substitution, gives 1.
Since \( 1 \neq 13 \), \( p = 1 \) is not a solution to \( 4p - 3 = 13 \).
### Part (vi)
Equation: \( -3p - 2 = 10 \)
Given \( p = -4 \).
Substitute \( p = -4 \) into the equation:
[tex]\[ -3(-4) - 2 = 12 - 2 = 10 \][/tex]
Both sides of the equation are equal to 10.
Since \( 10 = 10 \), \( p = -4 \) is a solution to \( -3p - 2 = 10 \).
### Summary
To summarize, the given values are solutions to the equations as follows:
(i) \( x = 2 \): Not a solution
(ii) \( n = 2 \): Solution
(iii) \( x = -2 \): Not a solution
(iv) \( p = -3 \): Not a solution
(v) \( p = 1 \): Not a solution
(vi) [tex]\( p = -4 \)[/tex]: Solution
### Part (i)
Equation: \( x + 5 = 3 \)
Given \( x = 2 \).
Substitute \( x = 2 \) into the equation:
[tex]\[ 2 + 5 = 7 \][/tex]
The right-hand side of the equation is 3, but the left-hand side, after substitution, gives 7.
Since \( 7 \neq 3 \), \( x = 2 \) is not a solution to \( x + 5 = 3 \).
### Part (ii)
Equation: \( 8n + 5 = 21 \)
Given \( n = 2 \).
Substitute \( n = 2 \) into the equation:
[tex]\[ 8(2) + 5 = 16 + 5 = 21 \][/tex]
Both sides of the equation are equal to 21.
Since \( 21 = 21 \), \( n = 2 \) is a solution to \( 8n + 5 = 21 \).
### Part (iii)
Equation: \( 4x + 3 = 5 \)
Given \( x = -2 \).
Substitute \( x = -2 \) into the equation:
[tex]\[ 4(-2) + 3 = -8 + 3 = -5 \][/tex]
The right-hand side of the equation is 5, but the left-hand side, after substitution, gives -5.
Since \( -5 \neq 5 \), \( x = -2 \) is not a solution to \( 4x + 3 = 5 \).
### Part (iv)
Equation: \( 5p + 3 = 7 \)
Given \( p = -3 \).
Substitute \( p = -3 \) into the equation:
[tex]\[ 5(-3) + 3 = -15 + 3 = -12 \][/tex]
The right-hand side of the equation is 7, but the left-hand side, after substitution, gives -12.
Since \( -12 \neq 7 \), \( p = -3 \) is not a solution to \( 5p + 3 = 7 \).
### Part (v)
Equation: \( 4p - 3 = 13 \)
Given \( p = 1 \).
Substitute \( p = 1 \) into the equation:
[tex]\[ 4(1) - 3 = 4 - 3 = 1 \][/tex]
The right-hand side of the equation is 13, but the left-hand side, after substitution, gives 1.
Since \( 1 \neq 13 \), \( p = 1 \) is not a solution to \( 4p - 3 = 13 \).
### Part (vi)
Equation: \( -3p - 2 = 10 \)
Given \( p = -4 \).
Substitute \( p = -4 \) into the equation:
[tex]\[ -3(-4) - 2 = 12 - 2 = 10 \][/tex]
Both sides of the equation are equal to 10.
Since \( 10 = 10 \), \( p = -4 \) is a solution to \( -3p - 2 = 10 \).
### Summary
To summarize, the given values are solutions to the equations as follows:
(i) \( x = 2 \): Not a solution
(ii) \( n = 2 \): Solution
(iii) \( x = -2 \): Not a solution
(iv) \( p = -3 \): Not a solution
(v) \( p = 1 \): Not a solution
(vi) [tex]\( p = -4 \)[/tex]: Solution
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.